Improved adhesion of Y-TZP ceramics: A novel approach for surface modification - Vanderlei, Aleska D. [UNESP]; Queiroz, Jose R.C. [UNESP]; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (My University, 2014)
The aim of this study was to evaluate the effect of novel surface treatments of Y-TZP ceramics on initial shear bond strengths to resin cement. Seventy-two samples (7 × 6 × 5 mm) were randomly divided into 6 groups (n = 12): Group 1 (G1), no treatment; Group 2 (G2), tribosilicatization (TS); Group 3 (G3), vitreous application 1 + etching with hydrofluoric acid (HF); Group 4 (G4), vitreous application 1 + TS; Group 5 (G5), vitreous application 2 + HF etching; Group 6 (G6), vitreous application 2 + TS. Surface roughness (Ra) evaluation was performed by optical profilometry, scanning electron microscopy, and X-ray spectroscopy. The samples were silanized, and resin cement cylinders (3 x 2 mm) were built on the treated surfaces, light cured, and submitted to shear testing (1 mm/min). The failure mode was evaluated by scanning electron microscope. Bond strength data were statistically analyzed using 1-way ANOVA and Tukey's test (α = 0.05). Bond strength results were significantly affected by surface treatments (P = 0.0001). G5 and G3 presented increased Ra parameters and showed highest bond strength results (17.8 ± 5.5 and 13.3 ± 4.1, respectively). Failure modes were mainly mixed in all groups except for G1. The results confirmed that the approach of coating surface-conditioned Y-TZP with a vitreous material increased the initial shear bond strength to resin cement.
Keywords: Adhesion; Bond strength; Glaze; Surface treatment; Y-TZP